Factor Analysis of Maternal Knowledge on the Incidence of Stunting - Lina Wati; Nita anggina Nasution; Nahda Aurallia; Sahilatun Nashirah; Mutiara Rizki; Rosalinda Harahap; Moriana ulfa Siregar; Mushtofainal Akhyar; Nabila Syafira Hasibuan; Putra Apriadi Siregar (Universitas Islam Negeri Sumatera Utara, Medan, 2022)
Stunting is a nutritional problem that occurs in toddlers; this nutritional problem begins to appear when the child is two years old. Stunting is a condition where children experience failure in growth. This study aimed to determine mothers' knowledge about the incidence of stunting in Bagan Serdang Village, Pantai Labu District, Deli Serdang Regency. This research method is a quantitative study using questionnaires, observations, and a cross-sectional approach. The population in this study were mothers who had toddlers in Bagan Serdang Village. Sampling in this study uses Non-Probability Sampling with a Purposive Sampling technique. In the study, a study done in Bagan Serdang Village, the vast majority of respondents needed more knowledge, namely 21 respondents (70%) and nine respondents (30%). This is due to a lack of counseling and a maternal desire to understand what stunting is and how to avoid it. Due to the absence of maternal awareness about the frequency of stunting, stunting rates have occurred. The frequency of stunting in Bagan Serdang Village was determined to be five toddlers (16.7%), whereas 25 toddlers (83.3%) were not stunted or normal. From here, we know that the mother's knowledge about stunting is one of the causes.Some efforts must be made in Bagan Serdang Village to increase mothers' knowledge about stunting in infants and toddlers by counseling mothers on the importance of nutrition in toddlers so that the incidence of stunting can be reduced by promotive, preventive, and curative measures provided by the village in collaboration with health workers.